Case Report: Improved Height in a Patient With Myhre Syndrome Using a Combination of Growth Hormone and Letrozole - Wu, Hui; Wang, Xinli; Cui, Yunpu; Wang, Xuemei (Frontiers in Pediatrics, 2021)
Myhre syndrome is a rare disorder caused by a heterozygous mutation in the SMAD4 gene. Affected patients may exhibit dysmorphic facial features, intrauterine growth retardation, short stature, obesity, muscle hypertrophy, thickened skin, limited joint movement, hearing impairment, and varying degrees of psychomotor developmental disorder. Serious complications of the cardiovascular and respiratory system may be seen later in life. We report the case of a Chinese boy with Myhre syndrome presenting with a novel symptom of giant testicles where treatment with growth hormone combined with letrozole successfully improved his short stature. This case shows that letrozole combined with growth hormone can improve height in children with Myhre syndrome without adverse effects.